Determinan Prilaku Ibu Hamil Melakukan Pemeriksaan Kehamilan (Antenatal Care ) Pada Masa Pandemi 19 - Heryanti, Fitri Apriani (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2024)
This COVID-19 pandemic situation, many restrictions to almost all routine services including maternal and neonatal health services. Pregnant mothers become reluctant to puskesmas or other health care facilities for fear of becoming infected, the presence of a delayed pregnancy examination and class of pregnant mothers The lack of an ANC visit can cause danger to both mother and fetus such as the occurrence of bleeding during pregnancies due to the lack of detection of signs of danger. The aim of this study is to analyze determinants related to the behavior of pregnant mothers in performing pregnancy screening during the Covid 19 pandemic in BPM “S” in 2021. The study was conducted using the analytical Survey method using the cross sectional approach, the population of this study is all pregnant TM III mothers who made the ANC visit in January-November 2021. The samples were obtained by accidental sampling of 45 pregnant women in the third trimester who performed an ANC in December 2021. The results of the study using Chi Square analysis showed ρ value α ≤ 0.05 is that there is a defining relationship between the behavior of pregnant mothers performing ANC with Age (ρ value = 0.044 < 0.05), Education (ρ value = 0.013<0,05), Knowledge 0,05). Kknowledge (ρ value= 0.037< 0.05 ), Attitude (ρ value = 0.039 < 0.05) and Health Facilities (ρ value = 0.035< 0.05). Whereas the unrelated variables are maternal work (ρ value = 0.198 > 0.05) and Husband support (ρ value = 0.130 > 0.05). The Covid 19 pandemic does not prevent pregnant mothers from undergoing routine pregnancy checks.